Assessment of shoreline changes for setback zone establishment from Son Tra (Da Nang city) to Cua Dai (Hoi An city), Vietnam - Liem, Ngo Van; Bao, Dang Van; Bac, Dang Kinh; Cuong, Ngo Chi; Nga, Pham Thi Phuong; Burkhard, Benjamin; Chi, Giap Thi Kim (Vietnam Journal of Earth Sciences, 2020)
The most important function of the coastal setback is to minimize damage due to coastal erosion, climate change response, and sea-level rise. There are many directions and methods of researching and assessing coastal changes and coastal erosion. This study presents the results of the shoreline changes in the area from Son Tra (Da Nang City) to Cua Dai (Hoi An City), Central Vietnam based on remote sensing data from 1965 to 2019. Three methods are used to include End Point Ratio (EPR), Linear Regression Rate (LRR), and Weighted Linear Regression (WLR). The results show that the EPR method is effective when calculating the rate of shoreline changes only at two different times. For more objective and reliable calculation, it is necessary to assess the shoreline changes over time. Meanwhile, the LRR method was shown to be superior because all shoreline data were taken into account during the construction of the regression line. However, when there is much shoreline data with different reliability, the WLR method proved more superior because of limited objective errors. The results show that from 1965 to 2019, the coast of the Son Tra - Cua Dai area had quite complicated fluctuations, of which the northern area (Son Tra) tended to accretion, the central area tends to be alternate between accretion and erosion, while the south area (Cua Dai) is strong to very strong erosion. The coast with sudden changes is the Cua Dai area with the shoreline change envelope (SCE) reaching 512m. The results also allow us to divide the coast of the Son Tra - Cua Dai area into 30 segments. They are clustered into 8 groups with different levels of erosion and accretion. This is an important basis for the setback zone establishment in the study area.